Implementing the Project-Based Learning Model by Interviewing and Reporting Techniques to Improve Tenses Mastery - Zahrida, Zahrida; Kasmaini, Kasmaini; Elfrida, Elfrida (UNIB Press, 2025)
This research aimed at improving the students’ mastery on tenses through the implementation a Project-Based Learning model using interviewing and reporting techniques. Class Action Research was the design of this research and was conducted on the first semester students of class A in the English Education Study Program at the University of Bengkulu, enrolled in the Basic English Grammar course. The research involved 37 participants and was carried out over two cycles, each consisted of three meetings. The stages of the research included planning, action, observation, and reflection. The instruments used were test and observation checklist. The result of the test showed an increase in the percentage of students who scored ≥70, from 54% in cycle 1 to 81% in cycle 2, indicating 27% improvement. The result of cycle 2 also demonstrated that the success indicator of this research has been achieved by more than 75% students got score ≥70. It can be concluded that the implementation of Project-Based Learning model using interviewing and reporting techniques effectively improve students’ mastery of tenses by encouraging them to apply grammatical knowledge in both speaking (interviewing) and writing (reporting), thereby deepening their understanding of grammar.